Evaluation of antibacterial potential of oxazole sulphonamide indole derivative against BspA of T.Forsythia using in silico molecular docking and ADMET prediction. - N.Naveenaa; Parkavi Arumugam; Rajalakshmanan Eswaramoorthy (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Introduction: T. forsythia is an anaerobic gram- negative bacteria, is associated more frequently and/or in higher levels with various forms of the disease, including gingivitis, chronic and aggressive periodontitis.A surface as well as secreted protein BspA belonging to the leucine-rich repeat family was identified in T. forsythia.It is a surface molecule that binds both fibrinogen, and has been linked to bacterial colonization of the oral cavity. Materials And Methods: The 2D structure of ASA compounds were made using Chem -Draw. The 3D structure of the protein was retrieved from protein Database Bank (2XS3). The protein and ligand preparation were done as per standard protocol. The SwissADME and PRO-Tox online server used for Statistical Analysis: ANOVA (p<0.05), the docking are compared with the clinically proven drug results molecule. Results: The selected ligands 2,3,4show better interactions with the modeled protein within the binding sites. Ligands 2,3,4 obeys Lipinski‘s rule of 5 with low toxicity profile and gives better interaction score. Conclusion: These ligands can be validated and can be used as it has better absorption and no cytotoxicity.So they can be further evaluated for using it as a potent drug for periodontitis.